Cloud technologies, firm growth and industry concentration: Evidence from France - Bernardo Caldarola; Luca Fontanelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
Recent empirical evidence finds positive associations between digitalisation and industry concentration. However, ICT may not be all alike. We investigate the effect of the purchase of cloud services on the long run size growth rate of French firms. Our findings suggest that cloud services positively impact firm growth rates, with smaller firms experiencing more significant benefits compared to larger firms. This evidence suggests that the diffusion of cloud technologies may help mitigate concentration in the era of the digital transition by favouring the digitalisation and growth of smaller firms, especially when the cloud services provided are more advanced.
Keywords: L20; L25; O33; 330; cloud; ICT; concentration; firm growth rate; firm performance